Carnivorous Plants from Nepenthaceae and Droseraceae as a Source of Secondary Metabolites - Magdalena Wójciak; Marcin Feldo; Piotr Stolarczyk; Bartosz J. Płachno (Molecules, 2023)
Carnivorous plants are able to attract small animals or protozoa and retain them in their specialized traps. Later, the captured organisms are killed and digested. The nutrients contained in the prey bodies are absorbed by the plants to use for growth and reproduction. These plants produce many secondary metabolites involved in the carnivorous syndrome. The main purpose of this review was to provide an overview of the secondary metabolites in the family Nepenthaceae and Droseraceae, which were studied using modern identification techniques, i.e., high-performance liquid chromatography or ultra-high-performance liquid chromatography with mass spectrometry and nuclear magnetic resonance spectroscopy. After literature screening, there is no doubt that tissues of species from the genera Nepenthes, Drosera, and Dionaea are rich sources of secondary metabolites that can be used in pharmacy and for medical purposes. The main types of the identified compounds include phenolic acids and their derivatives (gallic, protocatechuic, chlorogenic, ferulic, p-coumaric acids, gallic, hydroxybenzoic, vanillic, syringic caffeic acids, and vanillin), flavonoids (myricetin, quercetin, and kaempferol derivatives), including anthocyanins (delphinidin-3-O-glucoside, cyanidin-3-O-glucoside, and cyanidin), naphthoquinones (e.g., plumbagin, droserone, and 5-O-methyl droserone), and volatile organic compounds. Due to the biological activity of most of these substances, the importance of the carnivorous plant as a pharmaceutical crop will increase.